Evaluasi Penataan Air Mikro terhadap Kualitas Air di Daerah Reklamasi Rawa Pasang Surut, Pulau Rimau – Sumatera Selatan - NABILLA MEILASARI; Bakri Bakri (Jurnal Solum, 2026)
Tidal lowland reclamation areas generally experience water quality constraints due to high acidity and dissolved metal content, thereby requiring proper micro water management. This study aimed to evaluate the effect of micro water management on water quality in the reclaimed tidal swamp area of Pulau Rimau, South Sumatra. The research was conducted using a field observation method by applying water gate management at secondary and tertiary canals. Water quality parameters observed included pH, electrical conductivity (EC), and dissolved iron (Fe). Measurements were carried out periodically every two days for one month using portable pH meter, EC meter, and Fe test kit. The results showed that water pH ranged from 3.0 to 6.3, indicating acidic conditions, while EC values ranged from 1.15 to 1.99 mmhos cm⁻¹ and tended to increase during water retention periods. Dissolved Fe concentrations were generally low and mostly undetected during the observation period. Regression analysis indicated that rainfall had a moderate relationship with pH (R² = 0.530), but showed a very weak relationship with EC (R² = 0.001). These findings indicate that rainfall was more dominant in controlling water quality dynamics than micro water management treatments. Therefore, micro water management alone was insufficient to significantly improve water quality without integration with other land and water management strategies.